1997
DOI: 10.1055/s-0038-1656030
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study of Recombinant Factor VIII (RecombinateTM) in Previously Treated Patients with Hemophilia A

Abstract: SummaryA prospective, open-label multicenter investigation has been conducted to compare pharmacokinetic parameters of recombinant DNA-derived FVIII (rFVIII) and plasma-derived FVIII concentrate (pdFVIII) and to assess safety and efficacy of long-term home-treat- ment with rFVIII for subjects with hemophilia A. Following comparative in vivo pharmacokinetic studies, 69 patients with severe (n = 67) or moderate (n = 2) hemophilia A commenced a program of home treatment using rFVIII exclusively for prophylaxis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
121
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(131 citation statements)
references
References 45 publications
8
121
0
2
Order By: Relevance
“…11 A prospective open label multicenter study was then conducted to compare the pharmacokinetics of rFVIII with a plasma-derived FVIII (pdFVIII) and to assess the safety and long-term home-treatment efficacy with rFVIII for individuals with hemophilia A. 12 Sixty-nine patients with hemophilia A (67 severe, 2 moderate) participated in a trial for a median of 3.7 (1.0 to 5.7) years. At study entry, 44 were HIV seropositive and 25 were HIV seronegative.…”
Section: Recombinant Factor Viii: Recombinate/bioclate ®mentioning
confidence: 99%
“…11 A prospective open label multicenter study was then conducted to compare the pharmacokinetics of rFVIII with a plasma-derived FVIII (pdFVIII) and to assess the safety and long-term home-treatment efficacy with rFVIII for individuals with hemophilia A. 12 Sixty-nine patients with hemophilia A (67 severe, 2 moderate) participated in a trial for a median of 3.7 (1.0 to 5.7) years. At study entry, 44 were HIV seropositive and 25 were HIV seronegative.…”
Section: Recombinant Factor Viii: Recombinate/bioclate ®mentioning
confidence: 99%
“…Studies have also shown that rFVIII and pdFVIII have similar in vivo half-life and recovery [4], with some data suggesting that mean peak response and recovery values are greater for rFVIII than pdFVIII [9]. The benefits of prophylaxis have been demonstrated in several studies [10,11] in which early onset prophylaxis appears to prevent joint damage [12].…”
mentioning
confidence: 99%
“…The safety and efficacy of rFVIII has been demonstrated in a number of clinical trials in previously treated and previously untreated patients, and in long-term and home treatment settings [4][5][6][7][8]. Studies have also shown that rFVIII and pdFVIII have similar in vivo half-life and recovery [4], with some data suggesting that mean peak response and recovery values are greater for rFVIII than pdFVIII [9].…”
mentioning
confidence: 99%
“…VIII lub cz. IX komórki jajnika chomika chińskiego lub nerki zarodka chomika [5,6]. Ostatnio pojawił się rekombinowany koncentrat cz.…”
Section: Rodzaje Koncentratów Cz VIII I Ixunclassified
“…Zawierał albuminę ludzką do stabilizacji białka końcowego, jak również białka zwierzęce i ludzkie w podłożu hodowlanym. Preparat taki nazwano koncentratem rekombinowanym pierwszej generacji [5]. Kolejnym ważnym etapem w procesie produkcji czynników krzepnięcia było wprowadzenie cukru jako stabilizatora zamiast albuminy.…”
Section: Rodzaje Koncentratów Cz VIII I Ixunclassified